Enset in Ethiopia: a poorly characterized but resilient starch staple. (31st January 2019) - Borrell, James S; Biswas, Manosh K; Goodwin, Mark; Blomme, Guy; Schwarzacher, Trude; Heslop-Harrison, J S (Pat); Wendawek, Abebe M; Berhanu, Admas; Kallow, Simon; Janssens, Steven; Molla, Ermias L; Davis, Aaron P; et al.
Abstract: Background: Enset ( Ensete ventricosum, Musaceae) is an African crop that currently provides the staple food for approx. 20 million Ethiopians. Whilst wild enset grows over much of East and Southern Africa and the genus extends across Asia to China, it has only ever been domesticated in the Ethiopian Highlands. Here, smallholder farmers cultivate hundreds of landraces across diverse climatic and agroecological systems. Scope: Enset has several important food security traits. It grows over a relatively wide range of conditions, is somewhat drought-tolerant, and can be harvested at any time of the year, over several years. It provides an important dietary starch source, as well as fibres, medicines, animal fodder, roofing and packaging. It stabilizes soils and microclimates and has significant cultural importance. In contrast to the other cultivated species in the family Musaceae (banana), enset has received relatively little research attention. Here, we review and critically evaluate existing research, outline available genomic and germplasm resources, aspects of pathology, and explore avenues for crop development. Conclusion: Enset is an underexploited starch crop with significant potential in Ethiopia and beyond. Research is lacking in several key areas: empirical studies on the efficacy of current agronomic practices, the genetic diversity of landraces, approaches to systematic breeding, characterization of existing and emerging diseases, adaptability to new ranges and land-use change, the projected impact of climate change, conservation of crop wild relatives, by-products or co-products or non-starch uses, and the enset microbiome. We also highlight the limited availability of enset germplasm in living collections and seedbanks, and the lack of knowledge of reproductive and germination biology needed to underpin future breeding. By reviewing the current state of the art in enset research and identifying gaps and opportunities, we hope to catalyse the development and sustainable exploitation of this neglected starch crop.